Persistent amnion‐chorion membrane separation. Issue 2 (8th November 2018) - Gerson, Kristin D.; Modest, Anna M.; Hecht, Jonathan L.; Young, Brett C.
Abstract: Aim: Fetal membranes are composed of the amnion and chorion, which fuse during the early second trimester. Persistent separation confers increased risk of adverse perinatal outcomes. This study characterizes sonographic and placental findings associated with persistent amnion‐chorion (AC) membrane separation. Methods: This is a case series of 23 patients carrying singleton pregnancies with persistent AC membrane separation after 16 weeks' gestation diagnosed by ultrasound from 2010 to 2016 at our institution. Twenty placentas were available for analysis. Results: Obstetrical complications occurred in 13 (56.5%) cases; two (8.7%) cases resulted in intrauterine fetal demise. Fetal malformations were reported in eight (34.8%) cases. Four (17.4%) neonates were small‐for‐gestational age (SGA; <10th percentile). Placental size measured ≤10th percentile for gestational age in eight (40%) cases. Placental cord insertion was marginal or velamentous in eight (34.8%) cases. Maternal and/or fetal placental perfusion abnormalities occurred in 11 (55%) cases. Conclusion: AC membrane separation is associated with adverse obstetrical outcomes, placental abnormalities, including marginal and velamentous cord insertion, placental growth restriction and placental perfusion defects. This membrane complication is associated with increased incidence of fetal malformations in the absence of identifiable genetic etiologies.